New Zealand : 2019 Article IV Consultation-Press Release and Staff Report. (IMF Staff Country Reports; Country Report, 2019)
This 2019 Article IV Consultation with New Zealand discusses that economic growth picked up in early 2019 after slowing in the second half of 2018. The pickup mostly reflected a rebound in private business investment growth. Residential investment also strengthened, notwithstanding cooling housing markets. Bank lending continued to slow across all sectors, growing now broadly in line with nominal gross domestic product. The recent monetary policy easing fits the subdued inflation conditions and near-term risks to the outlook. Economic growth is only expected to remain close to potential on the back of a timely increase in macroeconomic policy support. The proposed higher capital conservation buffers would provide for a welcome increase in banking system resilience. The new requirements would increase bank capital to levels that are commensurate with the systemic financial risks emanating from the banking system. The new framework should also differentiate more between large and small banks. A stronger bank supervision regime would still be needed, to complement the higher capital requirements.